Contrastive analysis of business and marketing terms in English and Uzbek languages (Journal of Universal Science Research, 2023)
This article analyzes the lexical-semantic features of a number of terms related to business tourism in English and Uzbek languages. Tourism is one of the important aspects of the country's economy today. With the emergence of new types of tourism, new terms are emerging. In the last century, the terms related to various fields were adopted into the Uzbek language from European languages through the Russian language, and today they are being adopted directly from foreign languages.